Preparation of perovskite nanopowders by vibro-milling technique - Orawan Khamman (2018)
The potential of the vibro-milling technique as a simple method to obtain usable quantities of single-phase perovskite powders with nanosized particles was examined. A detailed study considering the role of both milling time and firing condition on phase formation and particle size of the final product was performed. Powder samples were mainly characterized using XRD, SEM and laser diffraction techniques. The calcination temperature for the formation of the desired phase was lower when longer milling times applied. More importantly, by employing an appropriate choice of the milling time and calcination condition, high purity perovskite nanopowders have been successfully prepared with a simple solid-state reaction method. © 2007 Elsevier B.V. All rights reserved.